Spray-dried natural orange juice encapsulants using maltodextrin and gum arabic - Naddaf, Luisana; Avalo, Belkis; Oliveros, Mariaudy (Rev. Téc. Fac. Ing. Univ. Zulia)
The microencapsulation of orange juice (Citrus sinensis L.) variety Valencia 12 Âº Brix (Juice A) and 8 °Brix (juice B) was performed by spray drying using maltodextrin encapsulants agents to 5 and 7% w/w and gum arabic to 2.5% w/w on the total weight of juice. Antiadherent agent was used tricalcium phosphate in a ratio of 1.5% on the total weight of the orange juice fed. The operating conditions of spray drying were: inlet temperature drying chamber between 127-133 °C, feed flow rate 8-21 mL/min, temperature of drying chamber outlet 76-88 °C, 4 KW power and compressed air pressure 1.5 bar. The treatments had highly significant differences for 99% confidence (p < 0.01), as also the solid soluble effects and concentration of encapsulant. The encapsulant that provides major protection for sugar and vitamin C was gum arabic to the Ad treatment (12 °Brix, 2.5 gum arabic, 1.5% tricalcium phosphate) and for moisture 3A treatment (12 Brix and 5% maltodextrin, 1.5% tricalcium phosphate).